Epidemiological features of Leishmania infantum in dogs (Canis lupus familiaris) suggest a latent risk of visceral leishmaniasis in the metropolitan area of Bucaramanga, Santander, Eastern Colombia (2023)
Visceral leishmaniasis (VL) is a disease caused by species of the Leishmania donovani complex that is mainly transmitted through the urban cycle involving dogs as the primary reservoir. In Colombia, the incidence of VL is increasing, along with the spread of potential vectors. This study aims to investigate the eco-epidemiological factors associated with Leishmania spp. infection in dogs from the Metropolitan Area of Bucaramanga (MAB), Santander, eastern Colombia, which is a region at risk for VL. We conducted molecular and serological surveillance of Leishmania spp. in 207 dogs from MAB to determine the epidemiological factors associated with infection. Subsequently, we carried out a molecular and serological analysis of phlebotomine and humans, respectively, in areas with a higher prevalence of infection, aiming to describe the main features associated with the transmission cycle. Out of the 207 dogs tested, 37 (17.8%, 95% CI = 12.6–23.1%) were positive for the presence of Leishmania antibodies by the IFAT test, and only 9 (4.3%, 95% CI = 1.55–7.15%) were positive for L. infantum by PCR. Multivariate analyses indicated that canine shelters and dogs with clinical signs commonly associated with canine VL had a higher prevalence of infection (P 0.05). In the entomological survey, 69 blood-fed female phlebotomine of the genus Lutzomyia were captured in canine shelters, among them, 55% were identified as Lutzomyia camposi, 29% as Lu. ovallesi, 7% as Lu. dubitans, 6% as Lu. torvida, and 3% as Lu. cayennensis. The identified meal sources of the phlebotomine included human, pig, avian, cattle, and porcupine (Coendou quichua) blood. However, no phlebotomine positive for Leishmania spp. were detected by molecular analyses. Finally, 14 humans who had frequent contact with L. infantum-positive dogs were analyzed through rK39 test, but none tested was positive for IgG/IgM antibodies. The molecular and serological analyses indicate the circulation of L. infantum in dogs from MAB, with canine shelters having the highest prevalence of infection. The entomological survey of canine shelters showed a significant diversity of phlebotomine without potential vectors of L. infantum, suggesting the presence of infection in dogs from these areas could take place in other locations or through other transmission routes. The circulation of L. infantum in multiple dogs from MAB suggests a latent risk of zoonotic transmission of VL in these cities.